2013
DOI: 10.1111/cid.12194
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Aesthetic Outcome with Post‐Extractive Implants with or without Soft Tissue Augmentation: A 2‐Year Randomized Clinical Trial

Abstract: This prospective study demonstrates the effectiveness of placing a soft tissue graft at the time of immediate implant placement in the aesthetic zone. At the 2-year follow-up, test group revealed a better aesthetic outcomes and stable facial soft tissues compared with control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
310
11
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(345 citation statements)
references
References 34 publications
12
310
11
12
Order By: Relevance
“…All studies used subepithelial connective tissue (CT) grafts. Immediate provisionalization was performed in six of 10 studies 24,44‐48 . Healing abutment was placed after immediate implantation in one study 29 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All studies used subepithelial connective tissue (CT) grafts. Immediate provisionalization was performed in six of 10 studies 24,44‐48 . Healing abutment was placed after immediate implantation in one study 29 .…”
Section: Resultsmentioning
confidence: 99%
“…Another three studies used a two‐stage approach 49–51 . Xenografts were placed after implantation in six studies, 24,44,45,47,48,50 and one study used a combination of xenograft and allograft 46 . Smokers were excluded in six studies 24,44‐46,48,51 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While in the entire test group all thin biotype cases obtained a satisfactory PES value only 75% of the control group obtained sufficient PES values. Good PES was obtained in 0% and 57% of the thin biotype cases in the control and test groups respectively (Miglioratti et al 2013). Bianchi & Sanfilippo (2004) observed a better emergence profile as well as an increased gingival thickness at immediate implants that received a subepithelial connective graft with respect to the control sites at 1 to 9 years.…”
Section: Soft Tissue Graftsmentioning
confidence: 98%
“…Some authors have tried to regenerate the missing bone between the implant surface and the socket walls using various bone augmentation techniques Benic et al 2012, Koh et al, 2011. Others have advocated thickening the soft tissues by means of a connective tissue graft at the time of surgery (Miglioratti et al 2013). Last but not least, experimental studies in dogs have suggested that a flapless approach could minimize buccal bone resportion (Blanco et al 2008).…”
Section: Introductionmentioning
confidence: 99%